Outcomes of Complete Excision and Roux-en-Y Hepaticojejunostomy for Choledochal Cysts: A Single-Center Experience - Asghar, Ibrahim; Muhammad Umar; Tahir, Ali; Laghari, Hamid Raza; Muhammad Arsalan; Moosa, Sohail (Indus Journal of Bioscience Research, 2025)
Background: Choledochal cyst is a developmental abnormality of the biliary tract that is related to repeated cholangitis, pancreatitis, biliary cirrhosis, and malignancy. The treatment of full cyst removal and Roux-en-Y hepaticojejunostomy is assumed to be the most effective, but the outcome can differ in children and adults because of the variation in the evolution of the disease and inflammatory alterations. Objective: To evaluate surgical and functional outcomes of complete excision and Roux-en-Y hepaticojejunostomy for choledochal cysts in pediatric and adult patients at a single tertiary care center. Methodology: The study involved a descriptive observation, which was carried out in Organ Transplant Unit, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences/ Gambat Medical College, Gambat, District Khairpur Mir’s, between May 2024 and May 2025. A total of 55 patients of all age groups who were diagnosed with choledochal cyst underwent total cyst excision and then Roux-en-Y hepaticojejunostomy. Clinical findings before operation, radiological categorization, variables during operation, early postoperative complications, and late outcome were noted down. The comparison was performed through the proper statistical tests with p